2008
DOI: 10.5194/acp-8-3899-2008
|View full text |Cite
|
Sign up to set email alerts
|

Observations of HNO<sub>3</sub>, ΣAN, ΣPN and NO<sub>2</sub> fluxes: evidence for rapid HO<sub>x</sub> chemistry within a pine forest canopy

Abstract: Abstract. Measurements of exchange of reactive nitrogen oxides between the atmosphere and a ponderosa pine forest in the Sierra Nevada Mountains are reported. During winter, we observe upward fluxes of NO 2 , and downward fluxes of total peroxy and peroxy acyl nitrates ( PNs), total gas and particle phase alkyl and multifunctional alkyl nitrates ( ANs (g+p) ), and the sum of gaseous HNO 3 and semi-volatile NO − 3 particles (HNO 3(g+p) ). We use calculations of the vertical profile and flux of NO, partially co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
109
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 108 publications
18
109
0
Order By: Relevance
“…Bouvier-Brown et al (2009b) showed significant levels of sesquiterpene emissions that mostly react before escaping the forest canopy from branch enclosure experiments, supporting this argument. In addition, Farmer and Cohen (2008) argued that vigorous intra-canopy chemistry was evident at this site based on estimates of vertical gradients and fluxes of ANs, PNs, NO 2 and HNO 3 . Wolfe et al (2009) Fig.…”
Section: Possible Missing Hcho Sourcesmentioning
confidence: 99%
“…Bouvier-Brown et al (2009b) showed significant levels of sesquiterpene emissions that mostly react before escaping the forest canopy from branch enclosure experiments, supporting this argument. In addition, Farmer and Cohen (2008) argued that vigorous intra-canopy chemistry was evident at this site based on estimates of vertical gradients and fluxes of ANs, PNs, NO 2 and HNO 3 . Wolfe et al (2009) Fig.…”
Section: Possible Missing Hcho Sourcesmentioning
confidence: 99%
“…To test this hypothesis, for each mechanism, box model runs were performed at a series of different NO x and isoprene emission rates, so that an O 3 isopleth plot could be constructed, similar to those found in Dodge (1977) and Sillman and He (2002). In general, all mechanisms produce the same overall behaviour of increasing O 3 with increasing isoprene and NO x emissions.…”
Section: Mechanism Intercomparison With a Box Modelmentioning
confidence: 99%
“…The degree to which NO x is regenerated from isoprene nitrate degradation remains uncertain (Fiore et al, 2012;Xie et al, 2013) and has a significant effect on the O 3 response to isoprene emission changes . Fourth, dry deposition of isoprene nitrates, which may represent an important NO x sink O. J. Squire et al: Influence of isoprene chemical mechanism on modelled tropospheric ozone 5125 in isoprene-rich regions, is also uncertain, with measured deposition velocities ranging from 0.4 cm s −1 (Shepson et al, 1996) to 2.7 cm s −1 (Farmer and Cohen, 2008). Finally, there is evidence for the importance of O 3 -initiated isoprene nitrate degradation (Lockwood et al, 2010) and fast photolysis of isoprene nitrates (Müller et al, 2014).…”
mentioning
confidence: 99%
“…Measurements of total RONO 2 by thermal dissociation laser induced fluorescence (Day et al, 2002) have shown that RONO 2 account for a substantial fraction of oxidized nitrogen (NO y = NO + NO 2 + NO 3 + total peroxy nitrates + total alkyl and multifunctional nitrates + HNO 3 + 2*N 2 O 5 + HONO +...) in urban (Rosen et al, 2004;Cleary et al, 2005;Perring et al, 2010;Farmer et al, 2011) and rural (Murphy et al, 2006;Farmer and Cohen, 2008;Day et al, 2009;Perring et al, 2009a;Beaver et al, 2012) locations as well as downwind of the continents . Isoprene nitrates are thought to be a large fraction of the organic nitrates.…”
Section: Introductionmentioning
confidence: 99%